(untitled) (New York, 2005)
This book constitutes the refereed proceedings of the 10th IMA International Conference on Cryptography and Coding, held in Cirencester, UK, in December 2005. The 26 revised full papers presented together with 4 invited contributions were carefully reviewed and selected from 94 submissions. The papers are organized in topical sections on coding theory, signatures and signcryption, symmetric cryptography, side channels, algebraic cryptanalysis, information theoretic applications, number theoretic foundations, and public key and ID-based encryption schemes.
Keywords: Coding theory,Cryptography,Mật mã,Lý thuyết mật mã